Lifecycle-based payment model for transcatheter aortic valve replacement: a retrospective observational study from finnish public healthcare - Olli Waris; Markku Eskola; Riikka-Leena Leskelä; Janne Hulkkonen; Aki Haukilahti; Paulus Torkki (Cost Effectiveness and Resource Allocation, 2026)
Abstract Background Traditional transcatheter aortic valve replacement (TAVR) reimbursement models, such as fee-for-service and DRG, focus on procedural costs and often fail to reflect long-term clinical value. In this study we compare economic and clinical outcomes of a novel lifecycle-based payment model introduced at Tampere University Hospital Heart Hospital, to a traditional lump-sum reimbursement model. Methods We conducted a retrospective, single-center economic analysis of 92 TAVR patients treated under the novel lifecycle model and 132 under the standard lump-sum model at Heart Hospital, Tampere University Hospital. Primary outcomes were total healthcare costs during years 2022 and 2023, one-year mortality, and NYHA class changes. Expected 10-year costs were derived using discounted cash flow (0%, 3%, 5%, 7%). Survival probabilities were recalculated using real-world Kaplan-Meier data and Gompertz extrapolation, utilizing a broader institutional registry cohort of 1,782 patients treated between 2014 and 2023, to refine the pilot model’s assumptions. Results Some baseline characteristics showed SMD-based imbalances that were addressed via IPTW weighting, whereas clinical outcomes remained similar across cohorts. Compared with the lump-sum model, the lifecycle model generated early budgetary savings of ~€2.7 million over the first four years. However, the discounted cumulative costs in the 10-year horizon were 5.9% higher. On an individual level, the 10-year discounted costs were even 30%–51% higher across risk strata. As survival rates exceeded the estimates set in the initial lifecycle model, divergence was driven by payments continuing beyond the breakeven point at which 62–72% of implants remained functional. Conclusions A lifecycle-based payment model for TAVR is feasible within a publicly funded healthcare system and provides early budgetary benefits. However, over a 10-year horizon, it can incur higher cumulative costs compared to lump-sum reimbursement. To enhance the economic impact, lifecycle payments should be dynamically adjusted based on data and clinical outcomes.